(untitled) (Journal of Engineering, 2014)
An experimental and numerical study has been carried out to investigate the forced convection heat transfer by clean or dusty air in a two dimensional annulus enclosure filled with porous media (glass beads) between two vertical concentric cylinders. The outer cylinder is of (82 mm) outside diameters and the inner cylinder of (27 mm) outside diameter. Under steady state condition; the inner cylinder surface is maintained at a high temperature by applying a uniform heat flux and the outer cylinder surface at an ambient temperature. The investigation covered values of input power of (6.3, 4.884, 4.04 and 3.26 W), Reynolds number values of (300, 700, 1000, 1500, and 2000) and dust ratio values (density number N) of (2, 4, 6 and 8). A computer program in MATLAB has been built to carry out the numerical solution by writing the governing equation in finite difference method. The local Nusselt number, the average Nusselt number, the contours of temperature field and velocity field were presented to show the flow and heat transfer characteristics. The results show that when clean air flow, the wall temperature gradually increases along the cylinder length in the direction of flow and decrease as Reynolds number increase while it increases with input power. For dusty air flow results show that the wall temperature gradually increases along the axial direction and increase with Reynolds number and with input power, and the maximum reduction in heat transfer will be 30 % for N=8 at Re=2000. Comparison was made between the present experimental and numerical results and it gives good agreement. The experimental and numerical Nusselt number follows the same behavior with a mean deviation of 12%.